Implementation of Corporate Social Responsibility at PT Adaro Energy Indonesia TBK - Nurul Huda (Universitas Muhammadiyah Palu, 2022)
Corporate Social Responsibility (CSR) or what is often known as Social and Environmental Responsibility (TJSL) is a form of company responsibility for its business activities. Where the company's operational activities certainly have positive and negative sides. Because in reality there are companies that still do not fully implement CSR, and it is even found that people do not trust these companies. This research aims to determine the extent to which PT Adaro Energy Indonesia Tbk (AEI) CSR implementation is carried out in accordance with applicable regulations and its impact on society and the surrounding environment. The research method used in this research is descriptive qualitative using sustainability report document data. The results of literature review observations based on Law Number 40 of 2007 and Government Regulation Number 47 of 2012, in the sustainability report AEI is considered to have implemented the CSR provisions. AEI's CSR which is implemented through the Turn on Change program includes Turn on Knowledge (education), Turn on Prosperity (community empowerment), Turn on Body (health), Turn on Culture (cultural preservation), and Turn on Sustainable (environment). AEI's CSR as a whole has also had a positive influence on society and the surrounding environment, such as in economic aspects, social aspects and environmental aspects.